A Case-Control Study of the Role of Cold Symptoms and other Historical Triggering Factors in Asthma Exacerbations. Issue 1 (3rd February 2000) - Tarlo, Susan M; Broder, Irvin; Corey, Paul; Chan-Yeung, Moira; Ferguson, Alexander; Becker, Allan; Warren, Peter; Simons, F Estelle R; Sherlock, Christopher; Okada, Marilyn; Manfreda, Jure
Abstract : BACKGROUND: Asthma exacerbations can be provoked by many triggers such as allergens, respiratory irritants and viral infections. The relative importance of these has not been prospectively documented in a case-control study. OBJECTIVE: To assess the relative importance of colds and other nonclimatic historical triggers of asthma exacerbations. METHODS: One hundred and nineteen adults and children with asthma in two Canadian cities participated in a one-year study of the role of exacerbating factors in asthma. Among these, 36 pairs (21 adult, 15 children) completed the case-control study. Patients were considered cases if they developed an acute asthma exacerbation and notified the centre within 24 h to allow the completion of a questionnaire and viral studies (cultures of nasopharyngeal swabs and serology). Control people with asthma were matched for sex, age and area of residence, had no exacerbation during the preceding four weeks and participated within 48 h of the case patients. RESULTS: Case patients versus control patients had a mean age of 22 years versus 20 years, 50% versus 55% were male, and 92% versus 86% had at least one positive aeroallergen skin test. Cases were more likely to have taken regular inhaled steroids (63% versus 33%, P<0.002). Cases were more likely to report the following within the previous week: fever (P<0.001), sore throat (P<0.001), increase in nasal symptoms (P<0.01), increased dust exposure (P<0.05), exposure to others with a cold (P<0.001) and, over the previous year, increased passive smoke exposure (P<0.05). Viral cultures and paired serology were negative. CONCLUSIONS: Symptomatic colds were the most common trigger of asthma exacerbations in the winter and spring, while a transient increase in dust exposure was also identified as a significant trigger. The association with chronic, passive smoke exposure and the use of inhaled costicosteroid medications likely reflected less stable pre-study asthma in those with exacerbations.